Strategi Penyutradaraan Video Animasi 2D “Seduhan Terakhir di Ambang Rimba” sebagai Media Literasi Lingkungan Tesso Nilo - Arkhadies Hanif Medina; Puspa Aulia Putri; Iwan Koswara; Rinda Aunillah Sirait (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
The development of the 2D animation entitled ”Seduhan Terakhir di Ambang Rimba” aims to serve as an environmental literacy medium to raise awareness of deforestation issues in Tesso Nilo National Park (TNTN), Riau. This animation adopts a magical realism directing strategy by utilizing symbolism and allegory, with the character Nilo, a Sumatran elephant, serving as an emotional representation of wildlife victims of deforestation. The work seeks to engage audiences through visual storytelling that prioritizes visual expression over explanatory narration. By employing motion comic techniques, parallax layering, and a contrasting color palette, the animation creates a profound atmosphere and evokes empathy toward the ecosystem damage occurring in Tesso Nilo. An eco-cinema approach is also applied, in which nature and wildlife function not merely as background elements but as primary subjects that shape the narrative and conflict. This study demonstrates that 2D animation can be an effective tool for conveying environmental literacy messages, fostering ecological awareness, and encouraging changes in attitudes toward the deforestation crisis. The resulting work is expected to contribute to the development of animation-based environmental literacy media and to offer a new perspective on conveying ecological issues in an emotional and impactful manner. This research also opens opportunities for further studies on the influence of animation on public behavior in supporting environmental conservation.